2018
DOI: 10.3390/ncrna4020011
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNA as Novel Players in the Pathophysiology of Schizophrenia

Abstract: Schizophrenia is associated with diverse changes in the brain’s transcriptome and proteome. Underlying these changes is the complex dysregulation of gene expression and protein production that varies both spatially across brain regions and temporally with the progression of the illness. The growing body of literature showing changes in non-coding RNA in individuals with schizophrenia offers new insights into the mechanisms causing this dysregulation. A large number of studies have reported that the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 159 publications
(195 reference statements)
0
29
0
Order By: Relevance
“…Over the past decade, dysregulated processing and altered abundance of a wide range of miRNAs have been associated with neurodegenerative disorders [5] and neuroblastoma [6]. Widespread changes in miRNA levels have also been observed in developmental brain disorders (DBDs) including autism spectrum disorders (ASD) [7], schizophrenia [8], intellectual disability (ID) [9], and epilepsy [10]. However, the precise miRNA-based mechanisms during brain development and in higher-order brain processing, including learning and memory and cognition, are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, dysregulated processing and altered abundance of a wide range of miRNAs have been associated with neurodegenerative disorders [5] and neuroblastoma [6]. Widespread changes in miRNA levels have also been observed in developmental brain disorders (DBDs) including autism spectrum disorders (ASD) [7], schizophrenia [8], intellectual disability (ID) [9], and epilepsy [10]. However, the precise miRNA-based mechanisms during brain development and in higher-order brain processing, including learning and memory and cognition, are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…These regulatory short ncRNAs are believed to manage expression of 20 to 60 percent of protein-coding genes in mammalian genomes [ 116 , 117 , 118 ]. At the same time, the dysregulation of miRNA expression can cause a number of psychiatric disorders, including SZ [ 12 ]. For a long time, miRNAs have been considered to be potential therapeutic agents themselves [ 119 ].…”
Section: Concluding Remarks: Perspectives Of Circular Rnas Therapymentioning
confidence: 99%
“…Genome-wide association studies (GWASs) have described only approximately 200 genome SNPs’ susceptibility loci for SZ [ 11 ]. Recent studies have shown that gene expression dysregulation, which is triggered by a number of epigenetic factors and aberrant expression of non-coding RNAs, could be one of the key causes of SZ and other psychiatric disorders [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs in the cytoplasm function as competing endogenous RNAs (ceRNAs) acting as molecular sponges for miRNAs, targeting proteins to regulate their expression, and suppressing translation by targeting mRNAs [13]. In addition to their various roles in cells, lncRNAs are also involved in various human diseases including cardiovascular diseases, autoimmune diseases, neurodegenerative disorders, and psychiatric disorders [10, 14, 15]. In particular, lncRNAs are reported to be closely associated with tumorigenesis [8].…”
Section: Long Non-coding Rnasmentioning
confidence: 99%